SISTEM PENDUKUNG KEPUTUSAN PENENTUAN BIBIT PADI UNTUK DAERAH PERTANIAN DI JALAN MASJID 2 LUBUK PAKAM DENGAN METODE SAW - Halimah (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2021)
Agriculture is one of the important sectors in Indonesia. Most of the Indonesian population depend on the agricultural sector, one of which is as a rice farmer. The source of research data on the selection of superior rice seeds is taken at Jalan Mesjid 2 Lubuk Pakam. The criteria used are water resistance, weather resistance, resistance to fertilizers and pesticides and soil compatibility. The benefits that can be obtained in this research are that it can make it easier to provide public information in determining the selection of rice seeds and get accurate results for selecting or selecting rice seeds for the community. By using a decision support system in choosing good rice seeds, it is able to reduce the level of risk of crop failure experienced by the community in the environment. The greatest value is in the Inpari 13 rice seed parity, which is the alternative chosen as an alternative in the selection of superior rice seeds.